2001
DOI: 10.1097/00000542-200105000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Lidocaine Decreases Sevoflurane Requirement for Adequate Depth of Anesthesia as Measured by the Bispectral Index ®   Monitor

Abstract: Epidural anesthesia reduced by 34% the sevoflurane required for adequate depth of anesthesia. This effect was not a result of systemic lidocaine absorbtion, but may have been caused by deafferentation by epidural anesthesia or direct rostral spread of local anesthetic within the cerebrospinal fluid. Lower-than-expected concentrations of volatile agents may be sufficient during combined epidural-general anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
92
0
6

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(100 citation statements)
references
References 0 publications
2
92
0
6
Order By: Relevance
“…However, it is interesting to note that intravenous lidocaine also failed to reduce volatile anesthetic requirements titrated to BIS in a study directly comparing intravenous and epidural administration of lidocaine. 9 Despite similar serum concentrations of lidocaine (2 lgÁmL -1 ) following both intravenous and epidural administration, only those patients given lidocaine in their epidurals showed evidence of anesthetic sparing. Previous research demonstrates that volatile anesthetics exert their immobilizing effect at the spinal level.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is interesting to note that intravenous lidocaine also failed to reduce volatile anesthetic requirements titrated to BIS in a study directly comparing intravenous and epidural administration of lidocaine. 9 Despite similar serum concentrations of lidocaine (2 lgÁmL -1 ) following both intravenous and epidural administration, only those patients given lidocaine in their epidurals showed evidence of anesthetic sparing. Previous research demonstrates that volatile anesthetics exert their immobilizing effect at the spinal level.…”
Section: Discussionmentioning
confidence: 99%
“…15 However, unlike the previous investigation by Ahmad et al, 6 the end-tidal sevoflurane concentrations in this study were compatible with BIS values in the range of 50 to 60. 2,16 The failure to demonstrate significant differences in recovery times between the two study groups was likely multifactorial. Firstly, the impact of a cerebral monitor in improving the titration of the maintenance anesthetic will be minimized when the device is used for relatively brief surgical procedures (28-31 min).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that neuraxial blockade produces inhibition of tonic afferent spinal signalling to the brain that produces general anaesthetic effects. Hodgson and Liu [11] observed that epidural lidocaine reduced by 34% the sevoflurane required to produce adequate depth of anaesthesia but intravenous lidocaine that had similar plasma lidocaine concentration to epidural did not. Doufas et al [12] found that sedation during epidural anaesthesia depended on sensory block level and was associated with detectable block-dependent alterations in the brainstem auditory evoked responses.…”
Section: Discussionmentioning
confidence: 99%